Relationship Of Service Management Quality With Antenatal Care Visit At PMB Suryani Medan City - Rizky Andriani Bakara; Balqis Nurmauli Damanik; Marta Imelda Br Sianturi (International Journal of Public Health, 2024)
This study delves into the correlation between service management quality and ANC visit attendance at PMB Suryani, Medan City in 2023. Using a quantitative approach with a structured questionnaire, the research reveals a significant association between service management quality and ANC visit attendance, with factors like staff competency, facility infrastructure, waiting time, and overall satisfaction playing crucial roles. Enhancing service management quality emerges as pivotal for encouraging regular ANC visit attendance, suggesting the need for improvements in staff training, facility infrastructure, waiting times, and patient satisfaction. By investing in these areas, PMB Suryani, Medan City can positively impact maternal and child health outcomes. Additionally, further research is recommended to explore additional factors influencing ANC visit attendance and assess long-term impacts on maternal and child health.